A Critical Review of Setting the Threat of Imprisonment for Children - Diah Ratu Sari Harahap (Budapest International Research and Critics University, 2022)
Discussions about the sentence for children always attract the public's attention because children are not spared from committing crimes. In Indonesia, a sentence for children has been regulated by Act Number 11 of 2012 concerning the Juvenile Criminal Justice System. This study aims to answer the following problems: 1.) Does the provision regarding the length of imprisonment for children who commit serious crimes in the Juvenile Criminal Justice System Act fulfil the principle of justice and can achieve the purpose of the sentence? 2.) What are the provisions regarding the length of imprisonment for children who commit serious crimes that meet the principles of justice and can achieve the expected sentencing goals in the future? This research is normative. The author realizes that children need to be protected from the trauma of imprisonment, but the suffering of the victims also needs to be considered.